USM AND IUNCBD SETS UP LINK FOR BIODIVERSITY STUDIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 1 March 2016 – Universiti Sains Malaysia (USM) through the Centre for Marine and Coastal Studies (CEMACS) is in discussions with the International University Network on Cultural and Biological Diversity (IUNCBD) to initiate research efforts on biodiversity and culture in Malaysia.